2021
DOI: 10.3390/molecules26206246
|View full text |Cite
|
Sign up to set email alerts
|

Automated Trimethyl Sulfonium Hydroxide Derivatization Method for High-Throughput Fatty Acid Profiling by Gas Chromatography–Mass Spectrometry

Abstract: Fatty acid profiling on gas chromatography–mass spectrometry (GC–MS) platforms is typically performed offline by manually derivatizing and analyzing small batches of samples. A GC–MS system with a fully integrated robotic autosampler can significantly improve sample handling, standardize data collection, and reduce the total hands-on time required for sample analysis. In this study, we report an optimized high-throughput GC–MS-based methodology that utilizes trimethyl sulfonium hydroxide (TMSH) as a derivatiza… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 59 publications
0
3
0
Order By: Relevance
“…The top apolar phase was transferred to a new tube and dried at 4 °C using refrigerated Labconco CentriVap Concentrator attached to − 84 °C CentriVap Cold Trap (Kansas City, MO, USA). Metabolites were derivatized by combining 30 μL of trimethyl sulfonium hydroxide (Sigma-Aldrich) (20 mg/mL) and 60ul of methyl tert-butyl ether (Sigma- Aldrich) in an automated manner as described in previous publication [ 23 ] A small volume (3 μL) of derivatized samples were injected via spitless injection into a Thermo Scientific Thermo Scientific Trace 1310 gas chromatograph loaded with a Phenomenex Zebron ZB- (Torrance, CA, USA) 1 ms fused silica capillary column (length = 30 m, I.D. = 0.25 mm, film = 0.25 μm), which was connected to a Thermo ISQ (Thermo Fisher Scientific) single quadrupole mass spectrometer.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The top apolar phase was transferred to a new tube and dried at 4 °C using refrigerated Labconco CentriVap Concentrator attached to − 84 °C CentriVap Cold Trap (Kansas City, MO, USA). Metabolites were derivatized by combining 30 μL of trimethyl sulfonium hydroxide (Sigma-Aldrich) (20 mg/mL) and 60ul of methyl tert-butyl ether (Sigma- Aldrich) in an automated manner as described in previous publication [ 23 ] A small volume (3 μL) of derivatized samples were injected via spitless injection into a Thermo Scientific Thermo Scientific Trace 1310 gas chromatograph loaded with a Phenomenex Zebron ZB- (Torrance, CA, USA) 1 ms fused silica capillary column (length = 30 m, I.D. = 0.25 mm, film = 0.25 μm), which was connected to a Thermo ISQ (Thermo Fisher Scientific) single quadrupole mass spectrometer.…”
Section: Methodsmentioning
confidence: 99%
“…Palmitate retention time was confirmed by standards. Total ion current peaks of different metabolites were normalized to the internal standard 3 deuterium labeled heptadecanoic acid [ 23 ].…”
Section: Methodsmentioning
confidence: 99%
“…The processing temperatures are lower, which may reduce unwanted reactions. TMSH is commonly used for the derivatization of free fatty acids prior to GC analysis (Ishida et al, 1999;Chiu and Kuo, 2020;Gries et al, 2021). However, it has been reported that TMSH is not efficient at derivatizing some of the unsaturated fatty acids (Ostermann et al, 2014).…”
Section: Derivatization For Gas Chromatographymentioning
confidence: 99%